The analogy of matchline sensing techniques for content addressable memory (CAM). Issue 3 (1st April 2020) - Mishra, Sandeep; Mahendra, Telajala Venkata; Hussain, Sheikh Wasmir; Dandapat, Anup
Abstract : Performance of a memory depends on the storage stability, yield and sensing speed. Differential input and the latching time of sense amplifiers are considered as primary performance factors in static random access memory. In a content addressable memory (CAM), the sensing is carried out through the matchline (ML) and the time for evaluation is the key to decide the search speed. The density of CAM is on a rise to accommodate a higher amount of information which increases the power dissipation associated with it. Issues such as the logical threshold variation and lower noise margin between match and mismatch are critical in the operation of a CAM. A good ML sensing technique can reduce the ML power with enhanced evaluation speed. This work provides an analogy of various ML sensing techniques based on their pre‐charging, evaluation and performance improvement strategies. Estimation on the power dissipation and evaluation time are made and in‐depth analysis on their power‐speed‐overhead trade‐off are carried on 64‐bit CAM macros.